Método de lectura comprensiva en la Educación Superior - Rivadeneira Zambrano, María Angélica (2024)
The book “Method of Comprehensive Reading in Higher Education” presents an innovative approach to teaching reading in foreign languages, grounded in sound psycho-didactic and epistemological principles. This work underlines the crucial importance of comprehensive reading in developing students’ critical and communicative skills, facilitating effective interaction with texts from diverse cultural matrices. The authors propose a model of comprehensive reading that skillfully integrates foreign language learning with vocational training. This approach emphasizes the contextualization of information and encourages self- learning, recognizing common deficiencies in students’ reading skills, such as difficulty in extracting specific information and discerning cultural values in foreign texts. To address these challenges, the book introduces an integrative procedure that promotes intercontextual understanding. This methodology facilitates the transfer of skills between the native and foreign languages, not only improving reading ability, but also preparing students for the communicative challenges of today’s globalized world. The text establishes a theoretical and practical framework that reconfigures the teaching-learning process of reading in foreign languages. In doing so, it highlights the relevance of these skills in the student's professional development and in their ability to interact effectively in international and multicultural contexts. This work offers an innovative and holistic perspective on the teaching of reading comprehension in higher education. Its integrative approach not only promises to improve students' language skills, but also equips them with essential tools to navigate the complex landscape of intercultural communication in the 21st century.